1992
DOI: 10.2307/1938731
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Thermal Ecology on the Mycosis of a Rangeland Grasshopper

Abstract: The clearwinged grasshopper, Camnula pellucida, exploits incident solar radiation to raise internal body temperatures above ambient levels. Under adequate temperature and light conditions, grasshopper body temperatures may exceed air temperatures by 10°—15°C with both nymphs and adults preferring to thermoregulate near 40°C, their optimal temperature for development. Comparison of age—specific phenology data collected from field sites with projections from computer simulation studies on grasshopper development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
111
1
3

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(120 citation statements)
references
References 26 publications
3
111
1
3
Order By: Relevance
“…This is especially true for ectotherms where ambient conditions constrain the physiological temperatures of both host and pathogen (Carruthers et al 1992;Blanford & Thomas 1999Jackson & Tinsley 2002;Blanford et al 2003;Klass et al 2007;Laine 2008;Lazarro et al 2008). Several experimental studies have now demonstrated an effect of temperature on the susceptibility and behaviour of ectotherm hosts and/or the virulence of their pathogens (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially true for ectotherms where ambient conditions constrain the physiological temperatures of both host and pathogen (Carruthers et al 1992;Blanford & Thomas 1999Jackson & Tinsley 2002;Blanford et al 2003;Klass et al 2007;Laine 2008;Lazarro et al 2008). Several experimental studies have now demonstrated an effect of temperature on the susceptibility and behaviour of ectotherm hosts and/or the virulence of their pathogens (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental studies have now demonstrated an effect of temperature on the susceptibility and behaviour of ectotherm hosts and/or the virulence of their pathogens (e.g. Carruthers et al 1992;Blanford & Thomas 1999;Ferguson & Read 2002;Jackson & Tinsley 2002;Wilson et al 2002;Yourth et al 2002;Woodhams et al 2003Woodhams et al , 2008Lazarro et al 2008). However, the functional mechanisms underlying these effects and their potential to affect the outcomes of infections under natural conditions are not well understood (Carey et al 1999;Jackson & Tinsley 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Not all pathogen-induced ''behaviours'' are detrimental to the host. In particular, high body temperatures generated by behavioural fever prevent pathogen growth in flies (Watson et al, 1993), grasshoppers (Carruthers et al, 1992) and locusts (Blanford et al, 1998) infected with fungi.…”
Section: Introductionmentioning
confidence: 99%
“…Kemp (1986) argued that there was no a priori reason for supposing a linear relationship between body temperature and ambient, and, furthermore, the relationship often proved non-linear over the full range of ambient temperatures. These objections have been overcome by fitting a non-linear Functional Ecology 1997 11, [705][706][707][708][709][710][711][712][713] regression curve, often incorporating solar radiation intensity into the model (Kemp 1986;Carruthers, Larkin & Firstencel 1992).…”
Section: Introductionmentioning
confidence: 99%